Diversity and Inclusion in Airline Organizational Culture : A Comparative Analysis of Avianca and Emirates - Cancino Merchán, Laura Gabriela; Martínez Pantoja, Yadira Ixchel; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how Avianca and Emirates integrate diversity and inclusion into their organizational cultures, examining the perceptions and experiences of each airline's employees and comparing the similarities and differences in their approaches. The research uses a quantitative method based on employee surveys focused on their perceptions of how each company addresses diversity and inclusion. The findings aim to offer insights into workplace practices that enhance employee satisfaction and company success in the aviation industry.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses